Adsorption of polycyclic aromatic hydrocarbons and inversion barriers of curved conjugated systems inside the molecular cage ExCage6+. Issue 11 (16th November 2017) - Denis, Pablo A.; Iribarne, Federico
Abstract: We investigated the hosting of planar and curved π systems by ExCage 6+ . The M06‐2X/6‐311G* method and including basis set superposition error (BSSE) corrections showed good agreement with the experimental free energy changes in solution. The mean absolute deviation (MAD) with respect to experiment was 1.3 kcal/mol. The M06‐2X/6‐31G* method exhibited a MAD of 2.1 kcal/mol, so it may be useful to investigate large systems. The good agreement between the M06‐2X/6‐311G*+BSSE results and the M06‐2X/6‐31G* ones was due to a fortuitous error cancelation between basis set incompleteness and BSSE. The interaction energies decreased linearly with the number of CC double bonds present in the PAH, but the shape of the PAH is an important factor in determining the binding strength. Finally, we studied how effective is ExCage 6+ in reducing the inversion barriers of buckybowls. For corannulene, sumanene and dibenzo[a, g]corannulene they are reduced by 2.0, 2.7, and 2.0 kcal/mol, respectively. Although these values indicate an induced fit catalysis by ExCage 6+, they are far from those values calculated inside bilayer graphene. Therefore, much work is necessary to replicate the reduction of inversion barriers observed for graphene. Abstract : The molecular cage ExCage 6+ decreases the inversion barriers of well curved conjugated systems, but the reductions are far from the values determined when stacking interactions are pushed to the limit. Host‐guest interaction energies show a linear dependence with respect to the size of the PAH, but the shape of the guest must be considered.